2020
DOI: 10.12688/f1000research.20904.1
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic regulation of oligodendrocyte myelination in developmental disorders and neurodegenerative diseases

Abstract: F1000 Faculty Reviews are written by members of the prestigious . They are F1000 Faculty commissioned and are peer reviewed before publication to ensure that the final, published version is comprehensive and accessible. The reviewers who approved the final version are listed with their names and affiliations. AbstractOligodendrocytes are the critical cell types giving rise to the myelin nerve sheath enabling efficient nerve transmission in the central nervous system (CNS). Oligodendrocyte precursor cells diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
30
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 162 publications
0
30
0
Order By: Relevance
“…Although the role of GluD1 in glia remains unknown, recent findings have shown that GluD1 mRNA is strongly expressed in certain types of glia—specifically in oligodendrocyte precursor cells (OPC), also called NG2+ cells (Larson, Zhang, & Bergles, 2016; Saunders et al, 2018). Although NG2+ cells often differentiate into myelinating oligodendrocytes throughout the brain (Antel et al, 2019; Berry, Wang, & Lu, 2020), this is not their only fate. These cells are also found in regions devoid of myelin, suggesting that they potentially have other functions (Larson et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Although the role of GluD1 in glia remains unknown, recent findings have shown that GluD1 mRNA is strongly expressed in certain types of glia—specifically in oligodendrocyte precursor cells (OPC), also called NG2+ cells (Larson, Zhang, & Bergles, 2016; Saunders et al, 2018). Although NG2+ cells often differentiate into myelinating oligodendrocytes throughout the brain (Antel et al, 2019; Berry, Wang, & Lu, 2020), this is not their only fate. These cells are also found in regions devoid of myelin, suggesting that they potentially have other functions (Larson et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…As put forward by this review and others [ 83 , 236 , 237 , 238 ], the epigenome is critical in the regulation of the OL lineage, including DNA methylation, histone modifications, chromatin remodeling, lncRNA, and miRNAs. Further studies analyzing how distinct epigenetic layers might contribute together to produce gene regulation would be essential to more precisely characterize the role of epigenetics on the oligodendroglial cell lineage.…”
Section: Discussionmentioning
confidence: 85%
“…Furthermore, lower mRNA levels of DNMT1 and DNMT3a and higher levels of BDNF were detected in cortical neurons after depolarization by KCl and a sodium channel agonist [ 235 ]. DNA methylation changes have also been observed in epilepsy, which are characterized by abnormal patterns of neuronal activity, but also following electroconvulsive stimulation in mice [ 236 , 237 ]. Among DNMTs, only DNMT3a was higher after stimulation, making it a candidate for activity-dependent de novo methylation [ 237 ].…”
Section: Epigenetic Changes Translate Environmental Cues Into Intrmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, ablation of such chromatin and epigenetic factors is expected to call forth structural and functional impairment in the developing or adult brain. Indeed, the impaired development of OL lineage caused by defective chromatin and epigenetic regulation of the various steps involved, is linked to pathophysiological changes leading to neurodevelopmental and neurodegenerative disorders (Maki et al, 2013;Ohtomo et al, 2018;Lu et al, 2019;Berry et al, 2020;Samudyata et al, 2020). Thus, it is plausible that the reported role of BAF155 and BAF170 in OL development (this study) partly highlights the white matter anomalies associated with documented syndromic and non-syndromic disorders associated with BAF complex dysfunction (Sokpor et al, 2017).…”
Section: Discussionmentioning
confidence: 70%